EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PADA PENERIMAAN DAN PENGELUARAN KAS DI PT. HARAPAN JAYA SENTOSA - Aznedra, Aznedra (Universitas Riau Kepulauan, 2015)
Accounting information system is one type of system that required by the company in dealing with day-to-day operations to generate information-information that is required by the management accounting and related parties in connection with other decision-making and policy-other policies. With the computerization will help usher of financial statements because the computer will automatically do a phased management of data- the data entered into the system. The study titled ?Analysis of Accounting Information System on Spending Cash and Cash Receipts in Company Harapan Jaya Sentosa. The purpose of this study was to determine the system used by the company for 7 years if it correct or not by using Standard Operating Procedure (SOP) company. The method used in this study is the method of direct observation. With interviews and literature study. Results form this study is the system used by the company for 7 years is correct and in accordance by using Standard Operating Procedure (SOP) company.Key word: Accounting Information System, cash receipts and cash disbursements.